2000
DOI: 10.1007/s001250051541
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones induce insulin resistance in 3T3-L1 adipocytes by reducing cellular content of IRS proteins

Abstract: Cardiovascular disease in postmenopausal women represents a major health care concern because a third of all women between the ages of 50 and 75 are thought to be affected and a sixth die of the consequences of artherosclerosis. Recent studies have clearly shown a strong correlation between insulin sensitivity and the development of cardiovascular disease [1±3]: thus factors that diminish insulin sensitivity in women have been the subject of considerable interest [4,5]. Evidence for an association between sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…We previously reported that, in the same population study, the ADH2*1 allele is associated with increased levels of LDL-cholesterol and high blood pressure, and an increased risk of cerebral infarction (Suzuki et al 2004). The concentration of insulin or resistance to insulin could be affected by sex hormones, sex hormone-binding globulin or obesity (Falkner et al 1999;Collison et al 2000). Therefore, as another possibility, the interaction of the ADH2*1 allele with several hormones associated with sex or lipids may decrease the insulin resistance in target tissues (Harada et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that, in the same population study, the ADH2*1 allele is associated with increased levels of LDL-cholesterol and high blood pressure, and an increased risk of cerebral infarction (Suzuki et al 2004). The concentration of insulin or resistance to insulin could be affected by sex hormones, sex hormone-binding globulin or obesity (Falkner et al 1999;Collison et al 2000). Therefore, as another possibility, the interaction of the ADH2*1 allele with several hormones associated with sex or lipids may decrease the insulin resistance in target tissues (Harada et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone, progesterone and estrogen have been proposed to cause insulin resistance by reducing the cellular content of insulin receptor substrate proteins which, in turn, results in a reduction in proximal insulin-stimulated signaling cascades (Collison et al 2000, Buren et al 2002, Garcia-Arencibia et al 2005. Several studies have provided evidence that glucocorticoids may play an important role in the physiological modulation of adipocyokines, and thus insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms by which estrogen modulates glucose uptake in mature adipocytes have not been well established. Collison et al previously showed, using fully differentiated 3T3-L1 adipocytes, that the decreased glucose uptake associated with estrogens (estrone, estradiol or estriol) was due at least in part to decreased cellular contents and an altered subcellular distribution of IRS proteins, in turn resulting in a reduction in proximal insulin signaling cascades [15]. However, under our experimental conditions, decreased tyrosine phosphorylation of IRS-1 protein occurred without IRS-1 protein degradation even during treatment with high doses of E2 or PPT.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, culture of 3T3-L1 adipocytes with high concentrations of estrogens (estrone, estradiol or estriol) resulted in a reduced ability of insulin to stimulate glucose uptake by attenuating insulin signaling events, leading to GLUT4 translocation to the plasma membrane [15]. This study suggests that these estrogens can modulate insulin sensitivity and contribute to the development of insulin resistance by acting directly on adipocytes, but the precise role of ER subtypes was not examined.…”
mentioning
confidence: 90%